Relationship between Breeder Characteristics and Adoption of Artificial Insemination in Bali Cattle - Sirajuddin, Sitti Nurani; Sudirman, Indriati; Bahar, Lydia Devega (European Journal of Sustainable Development, 2018)
Artificial Insemination was a program aimed at increasing the production of livestock as well as the income of farmers. The study was conducted from July to September 2017 in Balusu District, Barru District, South Sulawesi Province, Indonesia. The population in this study was the whole Bali cattle breeders who adopt artificial insemination technology located in District Balusu, Barru regency was as much as 548 spread in six villages.With using Slovin formula obtained by the sample amounted to 85 respondents. Kinds of data used in research these were qualitative data and quantitative data. Sources of data used were primary data and secondary data. Methods of data collection were observation and interview. Analyzes used in this research was Rank Spearman. The results showed that closely related to the adoption of IB, namely formal education and temporary business scale associated with the weak of age, family dependents and income. Keywords: adoption, artificial insemination, Bali cattle, characteristics